Field study of fish farming status in Basrah Governorate - Jassim, Abdul Amer R.; Almaktar, Mastafa A.; Jabir, A.A.; Hasoni, Khaled H. (Iraqi Journal of Aquaculture, 2022)
Field survey of Aquaculture farms in Basrah governorate was done during 2007. The study showed that there are 80 fish farm with total area of 773.5 donum, while it was 16 fish farm during 2003. 75 % of the fish farms were less than 25000 m² (10 donum). 53.9 % was excavated pond, 34.2% concentration by half ground pools and 11.8 % was dyke pond. About 87.5 % of it using pump while 12.5 % used tidal current for water supply. This study showed that 95 % of fishes source was from Marine Science Center Hatchery and the other were from natural environment. The poly culture was main type and composed 93.75 of fish farm, the rest fish farm used the monoculture type. The total number of farmed fish during 2007 was 514625 fish, common carp Cyprinus carpio was the main species (63.5 %) followed by grass carp Ctenopharyngodon idella (22.6 %), silver carp, Hypophthalmichthys molitrix (10.8 %), Acanthopagrus latus (1.39 %), mugil sp. (0.33 %) and Barbus sharpeyi (0.13 %). Work men were 312 person 52.8 % have intermediate school, 23.9 % illiterate, 15.7 % primary, 4.2 % bachelor, 2.8 % Diploma and 0.35 % secondary school. Most of the aquaculture activity was concentrated in north Basrah especially in Al-Mudeina Shire and Al-Qurna Shir.